Injections of adipose tissue-derived stem cells and stem cell lysate improve recovery of erectile function in a rat model of cavernous nerve injury - Albersen, Maarten (2010)
INTRODUCTION: Erectile dysfunction (ED) remains a major complication after radical prostatectomy. The use of adipose tissue-derived stem cells (ADSC) has shown promising results for the treatment of ED. However, the mechanisms of action for stem cell therapy remain controversial, with increasing evidence pointing to paracrine pathways. AIM: To determine the effects and to identify the mechanism of action of ADSC and ADSC-derived lysate in a rat model of cavernous nerve (CN) crush injury. METHODS: Thirty-two male Sprague-Dawley rats were randomly divided into four equal groups: one group underwent sham operation, while three groups underwent bilateral CN crush. Crush-injury groups were treated at the time of injury with intracavernous injection of ADSC, lysate, or vehicle only (injured controls). Erectile function was assessed by cavernous nerve electrostimulation at 4 weeks. Penile tissue was collected for histology. MAIN OUTCOME MEASURES: Intracavernous pressure increase upon CN stimulation; neuronal nitric oxide synthase (nNOS) content in the dorsal penile nerve; smooth muscle content, collagen content, and number of apoptotic cells in the corpus cavernosum. RESULTS: Both ADSC and lysate treatments resulted in significant recovery of erectile function, as compared to vehicle treatment. nNOS content was preserved in both the ADSC and lysate group, with significantly higher expression compared to vehicle-treated animals. There was significantly less fibrosis and a significant preservation of smooth muscle content in the ADSC and lysate groups compared to injured controls. The observed functional improvement after lysate injection supports the hypothesis that ADSC act through release of intracellular preformed substances or by active secretion of certain biomolecules. The underlying mechanism of recovery appears to involve neuron preservation and cytoprotection by inhibition of apoptosis. CONCLUSIONS: Penile injection of both ADSC and ADSC-derived lysate can improve recovery of erectile function in a rat model of neurogenic erectile dysfunction.